MEMPELAJARI KARAKTERISTIK FISIK BIJI KAKAO (Theobrema cacao L.) PADA SUHU PENGERINGAN YANG BERBEDA - Sri Waluyo; Tri Wahyu Saputra; Nikita Permatahati (The University of Lampung, 2021)
Drying is a common process step for agricultural grain products for ease of handling and to achieve the desired quality levels. One of the commodities that have high economic value produced by farmers in Lampung Province is cocoa beans. The drying process may change the physical properties of the cocoa beans and affect the processing of cocoa beans at a later stage. This study aims to determine the effect of drying temperature on changes in the physical properties of cocoa beans such as dimension, volume, weight, surface area, true density, bulk density, porosity, sphericity, and angle of repose. This research was applied to fresh non-fermented cocoa beans in testing. The cocoa beans were dried at temperatures of 40, 50 or 60oC. The research data were then statistically tested using paired sample T-Test at the 95% level to determine whether there is any effect of drying temperature on changes in its physical properties. The results showed a significant effect of drying temperature on weight, volume, geometric mean diameter (Dg), surface area, bulk density, porosity, and angle of repose of cocoa beans. Meanwhile, the sphericity and true density parameters did not significantly change. Keywords: cocoa beans, drying, physical properties